Generalized lymphangioma of the tongue: A rare cause of macroglossia - Amar A Shah; Khalid Mahmud; Anirudh V Shah (Wolters Kluwer Medknow Publications, 2020)
Generalized lymphangioma of tongue is a rare cause of macroglossia in children. It causes mechanical discomfort and functional and psychological disturbances. We report a case of macroglossia due to generalized lymphangioma in a 10 year old where partial glossectomy was done to achieve symptomatic relief.